Wer ist fremd an diesen Orten? Zur Bedeutung von Identität, Kultur, Raum und Zeit in den spanisch-nordafrikanischen Städten Ceuta und Melilla - Meyer, Frank (ERDKUNDE, 2004)
Ceuta and Melilla are two Spanish towns on the North African coast surrounded by the Moroccan national territory. However, the political-territorial conflict between Morocco and Spain over the two towns is still an acute problem. The inhabitants of the two towns are mainly Christians and Muslims, but small communities of Jews and Hindus are living there as well. These religious groupings in Ceuta and Melilla, which I have identified here, correspond to the subdivisions or classifications to their inhabitants made in the towns themselves. Religious denomination in Ceuta and Melilla is not only associated in everyday life with questions of belief or religious practices. Rather, the religions are mostly comprehensively perceived as cultures with corresponding and clear-cut values, traditions and customs as well as a territorial rootedness. It is for this reason that the official discourse of convivencia, i.e. peaceful and harmonious co-existence, refers to the four cultures. But the official representation of harmonious co-existence hardly corresponds to reality. The urban societies in Ceuta and Melilla can be seen as good examples of the significance and interconnection of identity, culture, space and time for human co-existence and the difficult relationship of the familiar and the strange.